Perbaikan Faktor Daya Menggunakan Motor Sinkron Dengan Metode Fuzzy Logic Control - Satria, Alvon; Ervianto, Edy (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
In many industry most of the load usage in the inductive characteristic condition. This condition getting lower power factor of system. If a low power factor will cause a decrease in the ability and officiency of the power system and affect the level of voltage. The use of synchronous motor in this paper is to produce reactive power to the optimal point power factor of system. The paper proposes is to improve power factor of the system using a synchronous motor. The addition of a fuzzy logic control method as the power factor controller so is always in good condition. Fuzzy logic giving command automatically to the synchronous motor to provide current to the system. Synchronous motor and fuzzy logic able to improve power factor of the system with a high of accuracy.Keyword : Synchronous Motors, Power Factor, Fuzzy Logic